Synthesis and Features of Luminescent Bromo- and Iodohectorite Nanoclay Materials - Santos HS; Norrbo I; Laihinen T; Sinkkonen J; Makila E; Carvalho JM; Damlin P; Brito HF; Holsa J; Lastusaari M (MDPI AG, 2022)
The smectites represent a versatile class of clay minerals with broad usage in industrial applications, e.g., cosmetics, drug delivery, bioimaging, etc. Synthetic hectorite Na-0.7(Mg5.5Li0.3)[Si8O20](OH)(4) is a distinct material from this class due to its low-cost production method that allows to design its structure to match better the applications. In the current work, we have synthesized for the first time ever nanoclay materials based on the hectorite structure but with the hydroxyl groups (OH-) replaced by Br- or I-, yielding bromohectorite (Br-Hec) and iodohectorite (I-Hec). It was aimed that these materials would be used as phosphors. Thus, OH- replacement was done to avoid luminescence quenching by multiphonon de-excitation. The crystal structure is similar to nanocrystalline fluorohectorite, having the d(001) spacing of 14.30 angstrom and 3 nm crystallite size along the 00l direction. The synthetic materials studied here show strong potential to act as host lattices for optically active species, possessing mesoporous structure with high specific surface area (385 and 363 m(2) g(-1) for Br-Hec and I-Hec, respectively) and good thermal stability up to 800 degrees C. Both materials also present strong blue-green emission under UV radiation and short persistent luminescence (ca. 5 s). The luminescence features are attributed to Ti3+/Ti-IV impurities acting as the emitting center in these materials.